Partial functionalisation of C4-symmetric tetramethoxyresorcinarenes - Tan, Daniel; Massera, C.; Mocerino, Mauro (TAYLOR & FRANCIS LTD, 2019)
© 2019 Informa UK Limited, trading as Taylor & Francis Group.